A visual perception study in landscapes subject to fires in South East Australia - Villagra Islas, Paula (BOSQUE, 2017)
Results of a visual perception study of landscapes subjected to prescribed burning regimes in South East Australia provided insight for improving fire management policies by considering the aesthetic dimension of landscapes. Preference and similarity data were collected during a series of photo-sorting interviews using photos as stimuli. Data were analyzed using a mix-method approach finding 10 landscape clusters. These were different in terms of the visual effect of different fire intensities over time and people’s knowledge about fire management practices.